Identifikasi bifurkasi kodimensi-2 pada sistem flutter dengan menggunakan kriteria Routh - Hartono, Hartono; Krisnawan, Kus Prihantoso (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2014)
In this paper, the codimension-2 bifurcation of a 2-parameter flutter system is identified using Routh’s criterion. Routh’s criterion is a tool to determine the number of roots of a real polynomial in the right half-plane. Based on this criterion, the regions borders of each parameter are determined in order to make the roots of flutter system characteristic equation have negative or positive real parts. A point is taken from each region and the phase portraits of the system are drawn. Based on the Routh’s table and the phase portraits, different dynamical structure that showing a pitchfork-hopf bifurcation is acquired. Key words: pitchfork-hopf bifurcation, flutter system, Routh’s criterion